A Technique To Improve MAC In WSN With Clock Synchronization - Neetu, N; Duhan, Bharti (International Journal of Computer Sciences and Engineering, 2020)
The wireless sensor network is the type of network, which is used to sense the environmental conditions like temperature, pressure etc. This type of network is generally deployed on the far places like oceans, forests and deserts, in such places, it is very difficult to recharge or replace battery of these sensor nodes. To reduce energy consumption of sensor nodes various techniques has been applied so far. Among these, one is by using LEACH protocol used for clustering in which cluster heads are selected on the basis of distance and energy. Then various modes are applied on this protocol such as active, sleep and ready mode. Nodes will go into the sleep, active and ready based on the priority of request for the channel access. The main problem exists in this is of clock synchronization due to which packet loss happened in the network which reduce network performance. In this paper, further enhancement will be proposed in the existing protocol by synchronizing the clocks of sensor nodes based on time lay technique. Then the proposed technique will be implemented in simulated in NS2. The graphical result will show that proposed technique performs better than existing protocol in terms of throughput, packet loss, energy, overhead, delay.